The History of the Brain and Mind Sciences : Technique, Technology, Therapy - Gavrus, Delia; Casper, Stephen T. (Book collections on Project MUSE., 2017)
How did technicians, epidemics, zoos, German exiles, methamphetamine, disgruntled technicians, modern bureaucracy, museums, and whipping cream shape the emergence of modern neuroscience?